2022
DOI: 10.3389/fnut.2022.961468
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Adherence to lifelines diet score and risk factors of metabolic syndrome among overweight and obese adults: A cross-sectional study

Abstract: BackgroundMetabolic syndrome (MetS) is one of the most significant public health issues worldwide, and diet quality is an important controllable environmental factor influencing the incidence of MetS. Numerous dietary scores have been established to assess compliance with dietary recommendations or eating patterns, many of which are not entirely food-based. Hence, Lifelines Diet Score (LLDS) was developed in response to the shortcomings of existing tools. This study aimed to assess any possible links between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…There is strong evidence for the direct causal effect of BMI on the risk of kidney function decline and CKD [ 28 , 29 ]. Additionally, participants with a low BMI were better at following a healthy diet than those with a high BMI [ 30 ]. Therefore, compared with participants whose BMI was ≥ 25 kg/m 2 , participants with lower BMIs had a reduced risk of CKD and kidney function decline.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence for the direct causal effect of BMI on the risk of kidney function decline and CKD [ 28 , 29 ]. Additionally, participants with a low BMI were better at following a healthy diet than those with a high BMI [ 30 ]. Therefore, compared with participants whose BMI was ≥ 25 kg/m 2 , participants with lower BMIs had a reduced risk of CKD and kidney function decline.…”
Section: Discussionmentioning
confidence: 99%
“…The food groups were specified as follows: Whole grains, refined grains, potatoes, dairy products, vegetables, fruits, legumes, meats, nuts and seeds, solid fat, liquid oil, tea and coffee, salty snacks, simple sugars, honey and jam, soft drinks, and desserts and snacks. The frequency with which people added salt or salty sauce to food while it was being prepared or cooked, before or during eating, and the frequency of consuming processed foods with a high salt content was used to assess dietary salt consumption [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among environmental and lifestyle factors, it has been shown that illiteracy, smoking, wine drinking, as well as underlying diseases such as hypertension and diabetes mellitus (DM) are the risk factors for ARC (6). Since obesity contributes to the etiology of DM and hypertension, it may affect the risk of ARC (7)(8)(9). However, the results from epidemiological studies investigating the association between obesity and ARC are inconsistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%